(untitled) (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2022)
Electrical energy used for industrial, office, and household purposes is channelled through transmission and distribution. The amount of electrical energy from the generator depends on the energy produced by the turbine to the generator and the generator’s efficiency. Therefore, knowledge of the level of efficiency and the amount of power entering the generator at the power plant centre is needed to obtain maximum production and avoid generating unitâ€™s derating the. The average value of generator efficiency in one day using simulation is 99.67%, and manual calculation is 99.67%. The maximum value of compressor absorption in one day for simulation is 52.99 KJ/kg at 04.00, and for calculation, the manual is 52.99 KJ/kg at 04.00. The average value of compressor absorption in one day for simulation is 51.24 KJ/kg, and manual calculation is 51.24 KJ/kg. The highest generator loss is at ambient temperature 29.7 Â°C, 29.3 Â°C, 28,5 Â°C, 27,6 Â°C with a generator output power of 15 MW with a generator loss of 84465.30 Watt.